The role of initial radiologic and clinical manifestations in predicting the prognosis for pneumonia caused by H1N1 influenza virus - Göya, Cemil; Yavuz, Alpaslan; Hamidi, Cihad; Çetinçakmak, Mehmet Güli; Teke, Memik; Hattapoğlu, Salih; Duşak, Abdurrahim (Journal of Thoracic Disease, 2014)
Objective: The aim of this study is to investigate the prognostic values of initial radiologic findings and preexisting medical conditions in pneumonia caused by H1N1 influenza virus that were obtained during the novel swine-origin influenza A (H1N1) virus (S-OIV) pandemic spread. Methods: Thirty-nine patients hospitalized due to H1N1 infection between September and December 2009 were retrospectively evaluated regarding the radiologic and clinical aspects. The thoracic computed tomography (CT) findings of all patients were assessed and accompanying conditions that may raise the morbidity were stated. The patients were divided into two groups as those who needed the intensive care unit administration and those treated with brief hospitalization; initial radiologic findings and preexisting medical situations of patients were compared among both groups respectively in terms of their prognostic value. Results: In 39 patients with H1N1 infection (21 males and 18 females; mean age of 53.9±14 in range between 19 and 99 years); the necessity of intensive care was significantly higher in patients with solely chronic obstructive pulmonary disease (COPD) (P=0.008, Odds ratio: 27) or co-existence of COPD and malignity (Odds ratio: 13); however, no statistically significant difference between two groups was observed regarding the radiologic facts or other combinations of accompanying medical conditions in terms of any effects to the prognosis. Conclusions: In the H1N1 (S-OIV) pandemic, we observed that merely the contribution to the diagnostic process; the radiologic features have no significance as being prognostic indicator. Additionally; the superposition of H1N1 infection in patients with either COPD or COPD by malignity was stated to be a potential risk factor in terms of increased morbidity.